Einsatz von IT in der Buchbranche: Literaturbericht - Ann-Sophie Vorndran (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2020)
– Technology is taking over the world. Moreover, Artificial Intelligence or AI as the latest form of disruption seems to take over the work of creative workers: we find AI as the creator of oil paintings and as potential journalists. AI even takes the approach of creative writing. Therefore, the publishing industry sees itself disturbed by technology once more. However, is technology that new to this industry? This work aims to present the state of usage of information technology within the publishing industry by analysing relevant literature. The literature report includes academic as well as practical works. The report shows a lack of research in the field of usage of information technology in the book or publishing industry. Also, literature in this field is in general very little, so the research field itself needs to be addressed quite broad and sometimes literature has been found in publications that seemed to not have much in common with the actual topic of the report. Furthermore, it must be stated that most research and practical publications in this field are driven by only a few phenomena such as the ebook, XML, DRM or data as phenomenon in general, whereas larger fields such as the value chain as an organizing model are being left out.
urn:nbn:de:bvb:29-opus4-146003
Keywords: 330; Verlagswesen; Buch; Informationstechnik